Ethylene tetrafluoroethylene nanofibers prepared by CO2 laser supersonic drawing - A. Suzuki; H. Hayashi (eXPRESS Polymer Letters)
Ethylene tetrafluoroethylene (ETFE) nanofibers were prepared by carbon dioxide (CO2) laser irradiation of asspun ETFE fibers with four different melt flow rates (MFRs) in a supersonic jet that was generated by blowing air into a vacuum chamber through the fiber injection orifice. The drawability and superstructure of fibers produced by CO2 laser supersonic drawing depend on the laser power, the chamber pressure, the fiber injection speed, and the MFR. Nanofibers obtained using a laser power of 20 W, a chamber pressure of 20 kPa, and an MFR of 308 g•10 min–1 had an average diameter of 0.303 µm and a degree of crystallinity of 54%.